Effects of fertilizers on growth and leaf nutrient content of clonal oil palm seedlings - Charis Saliun (2019)
Caonal oil palm offers the potential for greater productivity because it is possible to establish uniform tree stands comprising identical copies (clones) of a limited number of highly productive oil palms. There is limited information on the most suitable fertilizer type, method and rates of application for these clonal seedlings. Toe same fertilizer type, method and · rates of application for D x P seedlings was used by Sawit Kinabalu Sdn Bhd for clonal seedlings. This research was therefore conducted to investigate the effects of various types, methods and rates of fertilizers on the growth and leaf nutrient content of clonal palm seedlings. Two separated factorial completely randomized design polybag experiments were conducted at Gomantong Estate, Kinabatangan, Sabah. Experiment one showed no significant differences between all fertilizer application methods and rates on the vegetative growth of the seedlings. Toe results show that conventional fertilizer application was adequate to be recommended for the clonal palm seedlings in order to achieve standard vegetative growth before field planting. Toe results of experiment two also showed no significant differences between fertilizer ratio and rates on the vegetative growth and leaf nutrient content of the clonal palm seedlings. Toe results of the leaf nutrient content from the experiments was above the standard optimum nutrients required by oil palm seedlings. Symptoms of disorder known as white stripe that normally affect D x P seedlings was shown by the clonal palm seedlings. White stripe symptom was mostly observed on the clonal seedlings treated with higher rates of N. Based on foliar analysis results these clonal seedlings exhibited B deficiency as low at 10 (ppm) or below. Based on the result on these experiments the standard operating procedures for fertilizers (method of application, rate of application and NPK ratio) practiced by the industry is sufficient for the clonal seedlings. For experiment 1, based on the monetary cost benefit analysis the slow release fertilizer was RM0.05 cheaper than the conventional fertilizer per seedling. For experiment 2, with 10% increase in rate, the conventional ratio (F2) is cheaper than Fl by RM0.01 and for F3 by RM0.02 per seedling.